Posterior Reversible Encephalopathy syndrome in allogenic bone marrow transplantation: Case report in a reference hospital of Peru - Bazán-Ruiz, Susy (2024)
Posterior reversible encephalopathy syndrome (PRES) is a rare neurological complication of allogeneic stem cell transplantation (incidence of 1.1-22%). Usually presents as a disorder of consciousness or encephalopathy, associated in most cases with headache, visual disturbance, Hypertension and epileptic seizures. Literature describes the presence of PRES in patients who have received immunosuppressive agents after Hematopoietic Stem Cells transplantation, including cyclosporine, tacrolimus, and sirolimus, as well as chemotherapy such as cyclophosphamide, vincristine, methotrexate, L-aspar, among others. Two cases of hematological patients with PRES are presented, and a review of the literature on PRES after Hematopoietic Stem Cells transplantation.